Education Application Testing Perspective to Empower Students' Higher Order Thinking Skills Related to The Concept of Adaptive Learning Media - Hernawan Sulistyanto; Sofyan Anif; Sutama; Sabar Narimo; Anam Sutopo; Muhammad Izzul Haq; Gamal Abdul Nasir (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2022)
This article aims at arguing for the importance of the testing step when designing an educational application by taking a case study from the development of adaptive learning media. The media contains a set of in-struments that are specifically built to empower students' critical thinking skills. Three aspects that are con-sidered in testing this educational application are application validity at each stage of system development, measurement of the final system feasibility test for user needs, and system implementation by running learning media on the test sample. Implementation of testing on application products is carried out accord-ing to system requirements and models. The existence of the characteristics of adaptive media and the diver-sity of menus in the application implies the importance of doing a lot of improvisation when carrying out tests, such as determining the right test cases, choosing the appropriate test model and method, determining a suitable test environment, and considering several other aspects aimed at optimizing test results. obtained in order to ensure the quality of learning media products. This study analyzed the test data using Likert scale as an interpretation of the results of the validation assessment from the experts by referring to certain perceived standards of assessment. Meanwhile, the analysis of the data from the feasibility test results from a sample of 20 students using the system usability scale (SUS) instrument. The technique to test the effec-tiveness was using a pretest-posttest control group design with a sample of 98 students. Parametric/non-parametric data analysis was then applied to analyze the data on the results of testing the effectiveness or efficacy of adaptive media products in improving students' higher order thinking skills (HOTS). Based on the testing steps applied to the application of adaptive learning media, the results obtained that the product was considered feasible and effective in empowering students' HOTS. The study concludes that the educa-tional application testing that has been carried out is able to provide an objective and independent view of the application of adaptive learning media which will be useful in operational functions to understand the level of effectiveness in its implementation before being widely used in learning.